SIFAT PAPAN WOL KAYU SEBELAS JENIS KAYU DARI SUMATRA SELATAN DAN JAWA BARAT - I M Sulastiningsih; Rozak Memed; Paribroto Sutigno (Jurnal Penelitian Hasil Hutan, 1988)
The  results  of  laboratory  test of wood-wool   board properties  manufactured  from  11 individual  wood  species obtained from  South  Sumatra  and  West Java are reported  in this paper. The tests comprising board density, moisture content, thickness reduction due to  compression   and  bending  strength.The study  reveals that average yield  of  wood-wool is 315 kg per cubic  meter  of log input. The physical and mechanical properties   of   wood-wool   board  from  five  wood  species. mineralized   with  CaCl2  solution   were  in conformity with  the DIN  11.01  standard.  However,  only  four  wood  species  mineralized  with  Ca(OH)2 suspension  met  the standard  requirements.